Results of Internal Quality Assurance for Ureum Parameters at H. Andi Sulthan Daeng Radja Hospital - Asdinar, Asdinar; Hasanuddin, A R Pratiwi; Jusriani, Jusriani (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
Internal Quality Assurance (PMI) is a preventive and supervisory activity in the laboratory to ensure precise and accurate examination results. This study aims to evaluate the precision, accuracy, and types of analytical errors in PMI urea parameters in the laboratory of H. Andi Sulthan Daeng Radja Hospital, Bulukumba Regency. This descriptive study uses a mixed method with secondary data from PMI results for October–December 2023. The results showed that the average (Mean) urea value in October was 35.53 mg/dL, SD 1.77 mg/dL, CV 4.99%, and d 0.77%; November 35.48 mg/dL, SD 1.74 mg/dL, CV 4.89%, and d 0.88%; December 35.43 mg/dL, SD 1.81 mg/dL, CV 5.10%, and d 1.03%. The CV (precision) and d (accuracy) values are within the maximum control limits (CV ?8%, Bias ±10%). Westgard rule analysis showed violations of the 1-2s rule in October, in the form of warnings without affecting the validity of the control, while no violations were found in November–December. Conclusion: The precision and accuracy of urea parameters are in the good category based on the Levey-Jennings graph analysis and the Westgard rule.